2012
DOI: 10.1007/s10483-012-1585-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis and Brownian motion effects on boundary layer flow of nanofluid in presence of thermal stratification due to solar energy

Abstract: The problem of laminar fluid flow, which results from the stretching of a vertical surface with variable stream conditions in a nanofluid due to solar energy, is investigated numerically. The model used for the nanofluid incorporates the effects of the Brownian motion and thermophoresis in the presence of thermal stratification. The symmetry groups admitted by the corresponding boundary value problem are obtained by using a special form of Lie group transformations, namely, the scaling group of transformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Researchers concluded that heat transfer and solar collection processes can be improved through the addition of nanoparticles in the base fluids. Power tower solar collectors can benefit from the potential efficiency improvements that arise from a nanoparticle working fluid [14]. Nanofluid is a liquid suspended with nanometer-sized particles (diameter less than 50 nm) called nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers concluded that heat transfer and solar collection processes can be improved through the addition of nanoparticles in the base fluids. Power tower solar collectors can benefit from the potential efficiency improvements that arise from a nanoparticle working fluid [14]. Nanofluid is a liquid suspended with nanometer-sized particles (diameter less than 50 nm) called nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The movement of the particles was simulated for a period of 1,000,000s p using Eqs. (20) and (21). Since the starting position of the particles is at z = 0, the thermophoretic velocity of each particle was determined by dividing the final position of each particle in the z direction by the time of the simulation (1,000,000s p ).…”
Section: Simulation Results For Nanoparticlesmentioning
confidence: 99%
“…It is also apparent that there is a misconception that the Brownian movement and thermophoresis are independent phenomena. This has led to the erroneous practice of accounting for both the Brownian movement and the thermophoretic velocity in simulations [21][22][23] . The result is the ''double-counting'' of the thermophoretic effect.…”
Section: Continuum Description Of the Brownian Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though we now have a better understanding of turbulence modification by small solid particles, the mechanisms are complex and not easy to predict [7].…”
Section: Introductionmentioning
confidence: 99%